AS RELAÇÕES ENTRE INTELIGÊNCIA EMOCIONAL E BEM-ESTAR NO TRABALHO - Nascimento, Silvana Helal (2006)
Studies concerning to human behavior and health in labor environment, as well the best way to put worker s competences and skills into practice have been increasing its importance due to growing search for better organizational outcomes, growth of competitiveness in the market and business need for reaching effective teamwork and better performance of its staff. Managers look for resources and innovations in order to become possible the accomplishment of organizational targets with efficacy. Employees more competents, satisfied and involved with their work are also the ones who have high level of affective commitment with the organization. To the company, this can mean an increasing in productivity, reduction in number of absenteeism and turnover. The dimension health at work became relevant because well-being at work also means happier employees, with less probability of becoming physical, psych or moral sick. As a result, there is a reduction in costs related to worker s health reimbursement. On the other hand, the study about emotional intelligence in managers, suggests that people with high level of this kind of intelligence are able to keep deeper relationships and to build a safer social network, to help others who belong to their groups as well to develop a leadership where a solid team can be built and more effective communication with others, and to realize strategic business plans with more efficacy. The aim of this study it was to investigate the relation between emotional intelligence abilities and dimensions of well-being at work. The research was developed in a plastic and metallurgy segments company in a sample constituted by approximately 380 participants of both genders, aged between 18 and 58 years old. Data were obtained from a questionnaire filled by the participants. The questionnaire was consisted by four scales which measured the three components of well-being at work and the emotional intelligence abilities. The study results revealed that only three abilities of the emotional intelligence had relevant relation with well-being at work: empathy, social skills and self-motivation. More significant correlations between social skills and well-being at work were observed. Therefore, well-being at work seems to be associated to worker s intellectual and emotional capacities of being empathetic, to keep themselves self motivated and specially, to establish and to support their friendships (social skills).